Service quality in TINA quality of service trading in open networkarchitecture. - Hamada, T.
Enterprise-level QoS issues are discussed, from which QoS evolution paths are derived. Service-level QoS issues are identified, and they have been studied as a part of service quality issues in TINA service architecture. TINA stream binding and its role in the TINA QoS framework are presented. Soft guarantee of stream quality is proposed, which does not require strict resource reservation. The soft guarantee concept combined with TINA stream binding architecture supports progressive evolution of service quality
Keywords: QoS evolution paths; TINA; TINA Consortium; TINA-C.; Distributed object-oriented platform; Distributed processing environment; Enterprise-level QoS; Open network architecture; Pricing structure; Quality of service trading; Resource reservation; Service architecture; Service quality; Service-level QoS; Soft guarantee; Stream binding architecture; Stream quality